Effectiveness of the BOPPPS-MDT Model in Enhancing ECMO Training for ICU Staff: A Randomized Controlled Trial Assessing Knowledge, Skills, and Teamwork Outcomes - Zhou W; Huang L; Tang W (Advances in Medical Education and Practice, 2025)
Wenjun Zhou,1,* Langjing Huang,2,* Wenwen Tang3 1Department of Anesthesiology, The Sixth Hospital of Wuhan, Affiliated Hospital of Jianghan University, Wuhan, Hubei, 430015, People’s Republic of China; 2Department of Cardiovascular Medicine, Changsha Economic Development Zone Hospital, Changsha, Hunan, People’s Republic of China; 3Cardiovascular Department, Wuhan No.9 hospital, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenwen Tang, Cardiovascular Department, Wuhan No.9 hospital, No. 20 Jilin Street, Hongwei Road, Qingshan District, Wuhan, Hubei Province, 430080, People’s Republic of China, Tel/Fax +86 15902716596, Email 694586344@qq.comBackground: Extracorporeal membrane oxygenation (ECMO) is a life-saving therapy for critically ill patients, and effective training for ICU staff is essential. This study aimed to evaluate the effectiveness of the BOPPPS-MDT (Bridge-in, Objectives, Pre-assessment, Participatory Learning, Post-assessment, and Summary model integrated with Multidisciplinary Team) teaching model in enhancing ECMO training for ICU staff.Methods: A total of 108 ICU interns with diverse educational backgrounds and majors were randomly assigned to two groups: 54 in the control group and 54 in the experimental group. The experimental group received ECMO training using the BOPPPS-MDT model, while the control group received traditional training. Both groups underwent theoretical knowledge tests, performance evaluations, and satisfaction surveys.Results: There were no significant differences in baseline characteristics between the two groups. The experimental group scored significantly higher than the control group in 13 key theoretical knowledge areas (P < 0.05), case analysis, teamwork, and overall performance. The total score of the experimental group was significantly higher (P < 0.05). Cronbach’s α ranged from 0.757 to 0.905, confirming high reliability. The satisfaction rate for the BOPPPS-MDT method was 92.17%, significantly higher than the 75.42% for the traditional method (P = 0.001). The BOPPPS-MDT method enhanced engagement, interactivity, learning interest, and teamwork.Conclusion: The BOPPPS-MDT teaching model significantly improved ECMO training outcomes and student satisfaction compared to traditional methods. Keywords: BOPPPS-MDT teaching model, intensive care unit, oxygenation of extracorporeal membrane oxygenation, teaching effectiveness, learning outcomes, satisfaction survey